2017
DOI: 10.15605/jafes.032.02.08
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Mild Cognitive Impairment among Elderly Filipinos with Type 2 Diabetes Mellitus

Abstract: Objectives. This study aims to identify factors associated with mild cognitive impairment (MCI) among elderly Filipinos with Type 2 diabetes mellitus.Methodology. This is an analytic cross-sectional study involving 133 elderly (≥60 years old) with Type 2 diabetes mellitus consecutively sampled from the General Medicine and Diabetes Clinics of the Philippine General Hospital. Eligible subjects were interviewed to gather demographic and clinical data. Body mass index, waist-hip ratio and mean blood pressure were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…Blood glucose abnormalities and insulin resistance were reported to be linked to cognitive impairment in patients with T2DM. 7,8,10 In comparison to a study done by Blanquisco et al 11 , low educational attainment was not a predictor of cognitive impairment. Smoking and lipid profile were comparable to both patients with normal cognition and cognitive impairment.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Blood glucose abnormalities and insulin resistance were reported to be linked to cognitive impairment in patients with T2DM. 7,8,10 In comparison to a study done by Blanquisco et al 11 , low educational attainment was not a predictor of cognitive impairment. Smoking and lipid profile were comparable to both patients with normal cognition and cognitive impairment.…”
Section: Discussioncontrasting
confidence: 54%
“…The prevalence was lower in contrast to the study of Blanquisco et al which only included Filipino patients more than 60 years old. 11 This study noted that 69.6% of the cognitively impaired patients were less than 65 years old (Table 1).…”
Section: Discussionmentioning
confidence: 83%
“…A cross-sectional study conducted in a Filipino population with an average 12-year T2D duration observed a higher rate of mild cognitive impairment (45%) than previous studies among Korean and Polish populations, which described lower prevalences (31.5% and 32.7%, respectively) [ 26 ]. Furthermore, patients in the Filipino study reported poor results in language and recall, in contrast with previous studies that observed a decline in executive functions [ 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 91%
“…Additionally, there is wide variability across the studies in the cognitive assessments ( Table 1 ), ranging from studies using simple screening tests to studies using neuropsychological batteries exploring several cognitive domains. In this regard, some studies have found a close relation between albuminuria and memory [ 11 , 14 , 16 , 25 , 26 , 31 ]. However, others have not found a close relation but, instead, have found associations with the processing speed or executive functions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation